Identification of Novel Small-Molecule ASGP-R Ligands - G. Majouga, Alexander; A. Ivanenkov, Yan; S. Veselov, Mark; V. Lopuhov, Anton; V. Maklakova, Svetlana; K. Beloglazkina, Elena; V. Binevski, Petr; L. Klyachko, Natalya; B. Sandulenko, Yuri; Y. Galkina, Natalia; E. Koteliansky, Victor (Current Drug Delivery, 2016)
During the past decade asialoglycoprotein receptor (ASGP-R) expressed predominantly by hepatocytes has attracted a considerable attention as a convenient biomolecular trap for targeted drug delivery. Currently, several selective galactose-containing ligands equipped by drug molecules, e.g. known anticancer therapeutics, as well as diagnostic tools are under active preclinical development. In this paper, we have carried out a rational in silico screening among the molecules available in ChemDiv collection and compounds provided by our colleagues to reveal potential ASGP-R binders. Thus, 3D molecular docking approach provided a set of 100 `high score` molecules that was subsequently evaluated in vitro using an advanced Surface Plasmon Resonance (SPR) technique. As a result, dozens of novel small-molecule ASGP-R ligands with high diversity in structure were identified. Several hits showed the binding affinity much more better than that determined for galactose and Nacetylgalactosamine which were used as reference compounds. The disclosed molecules can be reasonably regarded as promising molecular devices for targeted drug delivery to hepatocytes.
Keywords: docking